Biofilm-forming of Candida parapsilosis sensu stricto and its susceptibility profile in Venezuela - Moreno Calderón, Xiomara; Marcano-Vásquez, Mirexia Eva; Ferrara-Valvano, Giuseppe Antonio; Panizo-Domínguez, María Mercedes; García-Centeno, Nataly Johana (Kasmera, 2020)
One of the main consequences of biofilm development is resistance to antifungals. Biofilm-forming by Candida parapsilosis sensu stricto isolated from blood and its susceptibility profile was determined. Thirty strains of C. parapsilosis sensu stricto belonging to the Candidemia Network of the Mycology Department of the Instituto Nacional de Higiene Rafael Rangel-Venezuela, were evaluated by microplate quantitative method with violet crystal staining, and Sabouraud dextrose agar supplemented with Congo red qualitative method. The microdilution method was used to determine the susceptibility, according to the Clinical and Laboratory Standards Institute M-27 document. Biofilm formation of C. parapsilosis sensu stricto by both quantitative and qualitative method was 63% and 50%, respectively. Sensitivity, specificity, and positive and negative predictive values of the qualitative method were 61.1%, 23%, 78.6%, and 43.8% respectively, when compared with quantitative method. Planktonic isolates were 100% sensitive to amphotericin B and caspofungin, with variable susceptibility to azoles. Quantitative method is a reliable assay to determine biofilm formation, while qualitative method can be used as an initial screening assay. No relationship was found between susceptibility of planktonic isolates and the ability to biofilm-forming.